Fault masking as a service. (3rd February 2014) - Gülcü, Koray; Sözer, Hasan; Aktemur, Barış; Ercan, Ali Özer; Ranjan, Rajiv; Buyya, Rajkumar; Leitner, Philipp; Haller, Armin; Tai, Stefan
SUMMARY In SOA, composite services depend on a set of partner services to perform their tasks. These partner services may become unavailable because of system and/or network faults, leading to an increased error rate for the composite service. In this paper, we propose an approach to prevent the occurrence of errors that result from the unavailability of partner services. We introduce an external Web service, dubbed Fault Avoidance Service (FAS), to which composite services can register at will. After registration, FAS periodically checks the partner links, detects unavailable partner services, and updates the composite service with available alternatives. Thus, in case of a partner service error, the composite service will have been updated before attempting an ill‐destined request. We provide mathematical analysis regarding the error rate and the false positive rate with respect to the monitoring frequency of FAS for two models. We obtained empirical results by conducting several tests on the Amazon Elastic Compute Cloud to evaluate our mathematical analyses. We also introduce an industrial case study for improving the quality of a service‐oriented system from the broadcasting and content delivery domain. Copyright © 2014 John Wiley & Sons, Ltd.